Impact of UV-C assisted drying treatment on the quality of Malaysian stingless bee honey - Afendi, Nurul Alissa; Abdul Karim Shah, Nor Nadiah (HH Publisher, 2022)
Stingless bee honey (SBH) has been the focus of various drying studies aimed atlowering the moisture content to an acceptable limit of less than 20%. The low moisture level of SBH has been found to slow yeast development and hinder the fermentation process, thereby prolonging its shelf-life. Conventionally, SBH is usually treated using thermal treatment to lower its moisture content. Due to issues with the quality degradation of thermal-treated SBH, other alternatives are being explored. Non-thermal treatment, namely ultraviolet (UV-C) assisted drying, has been proposed in this study with the expectation of replacing the conventional heat treatment. The UV-C closed system, when properly employed, mayprovide enough radiationenergy (below 40°C) to evaporate the moisture bound in the honey.Hence, this study was aimed at determining and correlating the effects of the UV-C assisted drying process on the quality of UV-C treated SBH. The experiment was carried out on SBH (Heterotrigona itama) under UV-C treatment with the stated parameters; wavelength: 254 nm, power: 7 W, UV-C dose: 8 mJ/cm2, thickness of SBH: 3 mm for 0, 30, 50, 75, and 120 min in a controlled environment (35 ±5% relative humidity and 25 ±5 °C temperature). The results of this study showedthat the moisture level of SBHwas below the critical moisture content of 20%, with the lowest moisture content recorded at 17.42% after 120min of UV-C treatment time (moisture loss: 3.5%) and the highest moisture content of 18.40% after 30 min of treatment time (moisture loss: 2.21%). However, the value of 5-hydroxymethylfurfural (5-HMF)obtained in this study was significantly high (above 80 mg/kg), which mightbe due to the high content of fructoseto glucose ratioin SBH. Nevertheless, while it has been demonstrated that UV-C assisted drying wasable to lower the moisture content of SBH, further study is necessary to evaluate its effectiveness without compromising on the quality of SBH.